A fractal approach to heterogeneous drug distribution: Calcium pharmacokinetics - Macheras, P. (PHARMACEUTICAL RESEARCH, 1996)
Purpose. To point out the importance of heterogeneity in drug distribution processes and develop a noncompartmental approach for the description of the distribution of drug in the body. Methods. A dichotomous branching network of vessels for the arterial tree connected to a similar venous network was used to describe the heterogeneity of blood flow in the successive generations of the networks. The relevant kinetics of drug distribution in the well perfused and the deep tissues was considered to take place under well stirred (homogeneous) and understirred (heterogeneous) conditions, respectively. Results. A `'homogeneous model'' with classical kinetics (which is mathematically equivalent with the one-compartment model) was developed for these drugs which are confined to well perfused (''well stirred'') spaces. A `'heterogeneous model'' was proposed for the drugs reaching understirred spaces using a decreasing with time rate coefficient (fractal kinetics) to model the diffusion of drug under heterogeneous conditions. The analysis of the model equations revealed that the homogeneous model can be considered as a special case of the heterogeneous model. Concentration-time plots of multiexponential type were generated using the heterogeneous model equation. The empirically used power functions of time for the analysis of calcium clearance curves, were found to be similar to the equation adhering to the heterogeneous model. Fittings comparable to multiexponential models were obtained when the heterogeneous model equation with only one adjustable parameter was applied to six sets of long period calcium data. Conclusions. The heterogeneous processes of drug distribution in the body can obey the principles of fractal kinetics. Calcium clearance curves were analysed with the heterogeneous model. The validity of multicompartmental models which are based on the concept of homogeneity to describe drug distribution should be reconsidered.
Keywords: calcium kinetics; drug distribution; fractal; Fractal kinetics; heterogeneity; Pharmacokinetics